Regulamentar para quê(m)? As representações sociais de prostitutas sobre a regulamentação da "profissão" - Afonso, Mariana Luciano (2014)
The general theme of this research is prostitution, known by common sense as the "oldest profession in the world", and always surrounded by much controversy, both nationally and internationally. Historically, the states are divided between their prohibition or regulation. Some social groups claim that prostitution should be regulated and recognized as a "job like any other," while others consider its exercise as a form of exploitation and commodification of the female body and expression of unequal power relations between men and women. Nationally, prostitution is already included in the Brazilian Code of Occupations, indexed with number 5198-05 in the category of "service provider". The Brazilian Penal Code does not criminalize the prostitutes, but punishes pimping. Since 1997 four law projects were shown to regulate prostitution, after many discussions, however, did not come to a conclusion about them, which seems to reflect the divergences in society about the subject. In 2012, Jean Wyllys proposed PL 4211/2012 which is currently in progress. In this interim, we propose to investigate what the main affected, the prostitutes themselves, think about the question. The theoretical and methodological framework is the Theory of Social Representations. The empirical field where this research was conducted is the central area of Sorocaba (SP), the region is historically known for sheltering prostitution. The subjects of this research are seven low-income prostitutes that exert their activity on the streets of this area. To understand the social representations of the subjects, direct observations were made and registered in a field diary and in-depth interviews, with semi-structured script were conducted. Institutions of the city with close contact with these women have been mapped: One of the Security Councils of Sorocaba, composed by tradespeople and police, one religious association, that is wing of the Catholic Church, and one Non- Governmental Organization (NGO), which works with Damage Reduction policy. Interviews with representatives of these institutions were conducted and documents produced by them were analyzed. To further understand the national context in which the theme is located, the content of the law projects, and the forces against and in favor of regulation were investigated, especially between State, Church, and social movements. It s concluded that the social representations of prostitutes are far from these speeches, and it s anchored in their own experience. They didn t know the particularities of each one of the law projects and they are against the regulation of prostitution.